1997
DOI: 10.1207/s15374424jccp2602_8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-Occurrence on the Referability of Internalizing and Externalizing Problem Behavior in Adolescents

Abstract: Assessed the effect of co-occurring versus not co-occurring internalizing and externalizing behavior problems on the reasons parents reported for clinical referral of their adolescent child. Reasons for referral were coded for 181 inpatient adolescents, and parent ratings of internalizing and externalizing behavior were obtained for a general population sample of 500 adolescents. Parents concurrently reported internalizing and externalizing behavior as reasons for referral less frequently (p < .0001) than woul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Medical providers in an HMO referred fewer than half of adolescents with a documented Substance Use Disorder to either substance abuse or mental health treatment (Scott et al 2004). Both parents (Weiss et al 1997) and teachers (Summers et al 1973) are more likely to identify externalizing than internalizing behavior, and the presence of an adolescent's externalizing disorder may interfere with parents' noticing commonly comorbid internalizing concerns (Weiss et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Medical providers in an HMO referred fewer than half of adolescents with a documented Substance Use Disorder to either substance abuse or mental health treatment (Scott et al 2004). Both parents (Weiss et al 1997) and teachers (Summers et al 1973) are more likely to identify externalizing than internalizing behavior, and the presence of an adolescent's externalizing disorder may interfere with parents' noticing commonly comorbid internalizing concerns (Weiss et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a response of "hot temper" would be coded as 95 to match CBCL Item 95, 'Temper tantrums or hot temper." This system was used reliably in previous studies (Eastman, 1997;Weiss, Jackson, & Susser, 1997;Weisz, Suwanlert, Chaiyasit, & Walter, 1987;Weisz & Weiss, 1991); our reliability report follows. To maximize use of the data, we added 39 codes (including one to designate "uncodable") to capture responses that did not fit CBCL items.…”
Section: Coding the Problem Listsmentioning
confidence: 96%
“…The relative likelihood of being referred for externalising or internalising problems is consistent with the low level of recognition of anxiety. Research has found that children with externalising problems are more likely to be referred than children with internalising problems (Weiss, Jackson, & Suesser, 1997;Weisz & Weiss, 1991).…”
Section: Discussionmentioning
confidence: 99%